Disease management and growth improvement in chilli and tomato using Trichoderma Spp. and flurascent pseudomonads - Rini C R (Department of Plant Pathology, College of Agriculture, 2005)
The study entitled “Disease management and growth improvement in chilli and tomato using Trichoderma spp. and fluorescent pseudomonads” was undertaken at College of Agriculture, Vellayani during 2001–2004. The pathogens viz., R. solani and Fusarium sp. causing seedling rot and wilt in chilli and tomato respectively were isolated from naturally infected plants collected from major vegetable growing tracts in Kerala and their detailed symptoms were studied. Among the different isolates of R. solani and Fusarium sp. R1t (R. solani from tomato), F1t (F. oxysporum from tomato) and F4c (F. solani from chilli) which produced maximum disease symptoms were selected for the study. Trichoderma spp. and fluorescent pseudomonads isolated from the rhizosphere and phyllosphere of healthy chilli and tomato plants collected from various locations of vegetable tracts and also from virgin forest soils of Kerala were tested for their antagonistic activity against the test fungi. Among the 26 native isolates of Trichoderma tested under in vitro conditions, TR17 and TR20 emerged as the efficient antagonists against R. solani and TR19 and TR22 against Fusarium sp. Out of the 56 native fluorescent pseudomonads tested the isolates P28 and P51 exerted maximum inhibition on R. solani and P20 and P28 were most inhibitory isolates against Fusarium sp. Pot culture experiments were conducted to assess the efficacy of biocontrol agents in managing the disease and enhancing the growth of chilli and tomato. Among the different antagonist treatments combined application of Trichoderma and Pseudomonas (TR17 + P28, TR20 + P28 and TR20 + P51) was highly effective and offered 100 per cent protection to tomato seedlings against R. solani. The growth and yield of the plants were also maximum with the combination treatments. In chilli also the combination of Trichoderma and Pseudomonas (TR20 and P28) was most effective with minimum disease incidence and maximum yield. Under greenhouse conditions, the wilt caused by Fusarium sp. was significantly reduced by the application of biocontrol agents. The maximum reduction in incidence and intensity of the disease was observed with the combination of TR22 + P28 in both the crops. The influence of TR22 + P28 on yield was also more promising in both chilli and tomato. The efficient isolates of antagonists obtained from the green house studies were further evaluated under field condition. Positive impact of BCAs on disease suppression and growth enhancement in chilli and tomato were noticed under field condition also leading to better economic yields based on the benefit : cost analysis done. Based on the characterization studies the isolates, TR17, TR20, TR19 and TR22 were identified as T. pseudokoningi, T. harzianum, T. viride and T. viride respectively and P28 was identified as P. fluorescens. In vitro studies on the mechanism of inhibition by the antagonists showed that competition, mycoparasitism and antibiosis were the mechanisms exhibited by the Trichoderma sp. against the fungal pathogens whereas fluorescent pseudomonad (P28) inhibited the pathogens through competition for nutrients and by the production of volatile antibiotics. Genetic analysis of the inhibitory character of Pseudomonas isolate (P28) clearly showed the plasmid borne nature of the inhibitory property. The multiplication and persistence of the antagonists in the rhizosphere soil was studied using antibiotic markers. The organisms showed satisfactory multiplication and persistence in the rhizosphere. Among the different solid substrates tested for mass multiplying T. harzianum and T. viride, sorghum grains, coirpith + neem cake (1 :1) and cowdung + neem cake (1 :1) + wheat flour (10 %) were the most favoured substrates by these organisms. Among these substrates coirpith + neem cake (1 : 1) at is original (35 %) or slightly higher (45 %) moisture sustained the viable population for longer period. For formulating P. fluorescens, talc at 40 per cent moisture was the best carrier. Economic feasibility of using bioagents in crop production was worked out and it was proved that application of bioagents resulted in increased plant stand with improved yield ultimately resulting in high economic return.